Transformasi Digital untuk UMKM Tangguh: Peran PKK dalam Edukasi Pemasaran Digital, Literasi Keuangan, dan Legalitas Produk - Rahmawati, Meylin; Kartini, Kartini; Irna, Rizky Agusriyanti; Nainggolan, Yohanna Thresia; Ayuningtyas, Niken; Jasmine, Nur Azizah Sekar (Lembaga Dongan Dosen, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) and the Family Welfare Empowerment (PKK) group of Karang Harapan Village have significant local economic potential but face challenges in digital marketing, financial literacy, and business legality. This community service program aims to enhance business capacity through training in digital marketing, strengthening financial literacy, and assisting with business legality processes. The program employed training, hands-on practice, and technical mentoring methods. The results show that all participants successfully established social media accounts, uploaded promotional content, prepared financial reports, and fulfilled part of their business legality requirements. Evaluation indicated an improvement in financial literacy of ≥30% and understanding of legality procedures of ≥80%. This program proved effective in enhancing business capacity and fostering an adaptive, professional, and sustainable MSME ecosystem Keywords: MSME, Digital Marketing, Financial Literacy, Business Legality, Community Empowerment